Szum w uszach: znane schorzenie współwystępujące z nadal nieznaną etiologią = Known frequent comorbidity with still unknown etiology - Krajčovičová, Zdenka; Meluš, Vladimir; Zigo, Rastislav; Kašlíková, Katarina; Grabczak, Pavel (Vilnius: Mykolas Romeris Universitetas)
Tinnitus is an example of comorbidity of unknown pathophysiology that significantly reduces subjective perception of quality of life. The incidence of the disability has an increasing trend. It is not surprising information, when we consider what the risk factors for tinnitus are: hearing loss, sound exposure, stress, anxiety, depression, ototoxic drugs, hypertension, and aging.
Keywords: tinnitus; hearing disorders; Hyperbaric Oxygen Therapy; szum w uszach; zaburzenia słuchu; hiperbaryczna terapia tlenowa